The Art and Science of Financial Econometrics: Applications, Challenges, and Future Directions - Rasyid, Abdul (Advances in Economics & Financial Studies, 2024)
This study delves into the realm of financial econometrics, aiming to comprehensively understand market dynamics and inform decision-making processes. Through a mixed-methods approach encompassing quantitative and qualitative methodologies such as surveys, interviews, and secondary data analysis, the research engages diverse stakeholders, enriching perspectives on financial econometrics. Findings reveal the efficacy of interdisciplinary research, methodological innovation, and stakeholder engagement in advancing the field, highlighting the imperative to bridge the gap between theoretical constructs and empirical realities. Embracing innovative methodologies and technologies emerges as crucial for navigating the complexities of modern financial markets, enhancing decision-making processes, and fostering innovation in financial econometrics